Antifungal activity of TiO2/AgBr nanocomposites on some phytopathogenic fungi. Issue 7 (1st June 2021) - Habibi‐Yangjeh, Aziz; Davari, Mahdi; Manafi‐Yeldagermani, Reza; Alikhah Asl, Shervin; Enaiati, Samira; Ebadollahi, Asgar; Feizpoor, Solmaz
Abstract: TiO2 /AgBr composites were synthesized by a simple ultrasonic strategy. Various instruments such as SEM, EDX, XRD, and FT‐IR were exploited to investigate their characteristics. Antifungal activities of the as‐obtained samples were assessed through the inactivation of Fusarium graminearum in the spore suspension method and mycelial growth inhibition of F. graminearum, Botrytis cinerea, and Sclerotinia sclerotiorum in the microdilution method. The results represented that the TiO2 /AgBr samples possess higher antifungal activities on F. graminearum spores than the pure TiO2 . The sample with 20 wt% silver bromide represented the highest inhibitory effect on the growth of F. graminearum so that all fungal spores were degraded in the initial times of the treatment process. The inactivation of fungal spores after 60 min was 35.2%, 97.8%, 98.9%, and 98.7%, in respect, for 5, 10, 20, and 30 weight percent of AgBr in the binary nanocomposites, while the inhibition rate was 13.4% for the pure TiO2. With increasing ultrasound irradiation time for more than 30 min, the inactivation rate constant decreased. It was also found that the antifungal activity of the nanocomposites without calcination was higher than those of the calcined materials. Considering the antifungal potential against phytopathogenic fungi and advantages such as simple synthesis and eco‐friendly nature, it seems that TiO2 /AgBr nanocomposites can be used instead of synthetic chemicals after additional field investigations and mass production. Abstract : TiO2 /AgBr nanocomposites synthesized by simple ultrasonic strategy showed the high antifungal activity against some phytopathogenic fungi and the sample with 20 wt% of AgBr represented the highest inhibitory effect.